Body Image, Body Shamming, Self- The Relationship Between Body Image and Body Shaming on Self-Esteem Among Final Year Students: The Relationship Between Body Image and Body Shaming on Self-Esteem Among Final Year Students - Fadhillah, Ummul (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2025)
Body shamming can cause a decrease in self- confidence in students, because body shamming is an act of bullying carried out through negative comments on other people`s physical appearance. body shamming can have causing depression, eating disorders, and explain the relationship between body image and body shamming in final year students. this research uses a quantitative approach using correlational methods. the total sample was 110 final year students. sampling was carried out using the purposive sampling method. the measuring tool in this research is the body image scale which is prepared based on the aspects proposed by cans and pruzinsky, the body shamming scale is prepared based on the aspects presented by duarte et al and the self- confidence scale is prepared based on the aspects stated by duarte et al. The results of the research show that the significance value of the body image variable on the self- confidence variable is 0,000< 0,05, so the variables are said to be correlation between and self- confidence is 0,025, so the correlation between variables is said tobe strong. meanwhile, the body shamming variable on self-confidence is 0,000> 0,05, do the variable is said to be uncorrelated. the correlation level between body shamming variable and self-confidence is 0,774, so the variable is said to be weak